Alternativas clínicas através de restaurações indiretas com inlays e onlays - Soares, Guilherme Maciel [UNESP] (2015)
Due to current great demand by the use of esthetic restorations made the improvement and development of new dental materials were more intense in order to meet the above requirements. While the indirect resins are viables, they are also conservative prosthodontic treatment that can be from unitary elements to small edentulous spaces. An analysis is the correct step to see in which situations would be better indicated its use, among them, the inlays/onlays. The inlays/onlays are made when the destruction of a tooth is significantly high, preventing a resin restoration confection. Currently there is a greater tendency to be held in ceromer or ceramic, being made in the laboratory from working models. The choice of material depends on the amount and the remaining tooth tissue condition and presence of antagonistic teeth restorations